Seroprevalence and risk factors associated with Equine piroplasmosis in North Egypt. (December 2020) - Selim, Abdelfattah; Khater, Hanem
Highlights: Equine piroplasmosis (EP) is a tick-borne protozoal disease affect equids, caused by Theileria equi and Babesia caballi. The seroprevalence rates for T. equi, B. caballi, and mixed infections were 36.5 %, 20 %, and 5.6 %. The risk of getting T. equi infection increased among grazing males over 10 years that infested with ticks during summer. The risk of getting B. caballi infection increased among grazing equines over 10 years that infested with ticks during summer. Abstract: Equine piroplasmosis (EP) is caused by Theileria equi and/or Babesia caballi and has economic importance particularly in equines reared in poor management systems. This study is based on cELISA test to study the seroprevalence of EP among 370 horses and 150 donkeys in four Governorates north Egypt. Additionally, its risk factors were studied for the first time. The seroprevalence rates 36.5 %, 20 %, and 5.6 % for T. equi, B. caballi, and mixed infections, respectively. The highest antibody levels against T. equi were detected in Kafr ElSheikh (40 %) and Giza (40.1 %) Governorates, whereas those of B. caballi were detected in Qalyubia (25 %) and Kafr ElSheikh (24.1 %) Governorates. Concerning T. equi, animals >10 years (OR = 2.06) were more likely to be infected with EP than those <5 years old. In addition, the seropositivity increased among grazing (OR = 5.7, 95 % CI: 1.73−19.27) males (OR = 1.8, 95 % CI: 1.23−2.61) infested with ticks (OR = 2.3, 95 % CI: 1.60−3.48) during summer (OR = 4.3, 95 %CI: 2.53−7.46); whereas the seropositivity of animals for B. caballi increased among grazing equines (OR = 7.8, 95 % CI: 1.05−58.25) over 10 years old (OR = 2.08, 95 % CI: 1.10−3.94) and infested with ticks (OR = 2.4, 95 % CI: 1.54−3.76) during summer (OR = 7.12, 95 % CI: 3.15–16.06). Therefore, EP is an important prevalent disease in Egypt and deserves further attention regarding the management system, treatment, and vector control.